Changes in waist circumference and the incidence of diabetes in middle-aged men and women. - Tina Landsvig Berentzen; Marianne Uhre Jakobsen; Jytte Halkjaer; Anne Tjønneland; Thorkild I A Sørensen; Kim Overvad (PLoS ONE, 2011)
Background Waist circumference (WC) is positively associated with diabetes, but the association with changes in WC (DWC) is less clear. We investigated the association between DWC and the subsequent risk of diabetes in middle-aged men and women, and evaluated the influence from concurrent changes in body mass index (DBMI). Methodology/principal findings Data on 15,577 men and 20,066 women from the Danish Diet, Cancer and Health study were analyzed. Anthropometry was assessed in 1993-97 and 1999-02. Information on diabetes was obtained from The Danish National Diabetes Register. Hazard ratios (HR) were calculated from Cox' proportional hazard models with individuals considered at risk from 1999-02 until December 31 2006. During 5.4 years of follow-up, 1,027 and 876 new cases of diabetes occurred among men and women, respectively. WC was positively associated with diabetes in both sexes also with adjustment for covariates and BMI. DWC was positively associated with diabetes in women, but not in men (HR per 5 cm change = 1.09 (1.04:1.15) in women, and 1.00 (0.94, 1.07) in men with adjustment for covariates, baseline WC, BMI and DBMI). Associations with DWC were not notably different in sub-groups stratified according to baseline WC or DBMI, or when individuals with diseases or diabetes occurring within the first years of follow-up were excluded. Conclusions/significance While this study confirmed that WC is positively associated with the risk of diabetes in middle-aged men and women, it surprisingly showed that changes in WC were not associated with the subsequent risk of diabetes in men, and only weakly positively associated with the risk of diabetes in women. Accordingly, these findings suggest that a reduction in WC may be a weak or insufficient or target for prevention of diabetes in middle-aged men and women.